(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Introduction As accounting faces growing challenges from financial opportunism, fraud rationalization, and intricate commercial transactions, the adaptability of Accounting Information Systems (AIS) within cooperatives becomes crucial. Recognizing AIS as information providers and the catalysts for AIS capabilities development can augment cooperative efficiency. This study investigates the usage status of AIS within micro-scale cooperatives in La Union and examines its impact. Method An electronic questionnaire was administered to 30 micro-scale cooperatives registered under the Cooperative Development Authority in La Union, spanning finance, agri-business, services, marketing, education, electricity, housing, and health sectors. Descriptive and inferential statistics were employed to analyze the collected data. Results and Discussion The findings reveal that manual accounting systems are predominantly used among various types of micro-scale cooperatives in La Union. Issues related to the risk of material misstatement are frequently encountered in these accounting systems. While there’s strong appreciation for the potential benefits of faster and more convenient accounting systems, there’s also hesitancy in adopting accounting software due to personnel discomfort. Conclusion and Recommendations Micro-scale cooperatives in La Union exhibit a level of comfort with their current accounting systems but also acknowledge the potential for improvement through modern technologies. The demand for the development of an online cloud-based accounting information system is evident. Based on the study’s results, the following recommendations are put forth: • Micro-scale cooperatives should consider transitioning to an online accounting information system to expedite organizational performance and facilitate informed decision-making through timely financial reporting. • Personnel should receive capacity-building training in using online accounting information systems, ensuring effective adoption and utilization. In a landscape marked by evolving financial challenges, the enhancement of accounting information systems holds the potential to not only streamline cooperative operations but also empower cooperatives to make well-informed decisions in a rapidly changing environment.